2014
DOI: 10.14233/ajchem.2014.17136
|View full text |Cite
|
Sign up to set email alerts
|

Removal Techniques of Nitrate from Water

Abstract: Nitrate pollution of water is a major environmental problem all over the world. Consequently, numerous techniques have been developed to remove or reduction of nitrate in water. A review of removal techniques of nitrate from water has been carried out in this paper. Recent literatures related to various techniques including reverse osmosis, ion exchange, electrodialysis, biological denitrification, chemical denitrification, adsorption methods using different adsorbents like carbon base, agricultural waste, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 63 publications
0
17
0
4
Order By: Relevance
“…In fact, ion exchange is a reversible reaction between an electrolyte and a complex, where NO 3ˉ and NO 2ˉ, which have a negative ionic charge, will bind to the positively charged sites on the anion exchange beads of IEMs [44,45]. For electrodialysis (ED), according to Mohsenipour et al [46], the feed water supplied should have a turbidity that is lower than 2.0 nephelometric turbidity units. Furthermore, the concentration of free chlorine in water should be less than 0.5 mg/L, while these of hydrogen sulfide and manganese levels should be lower than 0.3 mg L. With electrodialysis systems about 70-85% of the water that is supplied to the system is available for use as low NO 3ˉ water [47].…”
Section: Nitrate Removal Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, ion exchange is a reversible reaction between an electrolyte and a complex, where NO 3ˉ and NO 2ˉ, which have a negative ionic charge, will bind to the positively charged sites on the anion exchange beads of IEMs [44,45]. For electrodialysis (ED), according to Mohsenipour et al [46], the feed water supplied should have a turbidity that is lower than 2.0 nephelometric turbidity units. Furthermore, the concentration of free chlorine in water should be less than 0.5 mg/L, while these of hydrogen sulfide and manganese levels should be lower than 0.3 mg L. With electrodialysis systems about 70-85% of the water that is supplied to the system is available for use as low NO 3ˉ water [47].…”
Section: Nitrate Removal Techniquesmentioning
confidence: 99%
“…Mohsenipour et al [46] also reported the efficiency of NO 3ˉ removal by a biological denitrification method using Pseudomonas bacteria and carbon source (starch of 1%) for initial NO 3ˉ concentrations of 500 and 460 mg/L; the denitrification rates were respectively equal to 86 and 89% [49]. Furthermore, various conventional and nonconventional materials from different origins have been studied and conceived, as adsorbents, to limit the harmful effects of NO 3ˉ [23].…”
Section: Nitrate Removal Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tidak seperti proses nitrifikasi yang dapat berlangsung mudah asalkan terdapat jumlah dan jenis mikroba yang cukup disertai konsentrasi oksigen yang memadai, proses denitrifikasi lebih sulit terjadi karena harus dipenuhi syarat lain seperti tingkat keasaman yang optimal, dan adanya donor hidrogen dengan mikroba autotrof maupun heterotrof yang sesuai seperti Achromohaciet, Arinetobacter, Agrobacterium, Alcaiigenes, Arthrobacfer, Bacillus, Chromobacterium dan Corynebucterium [2]. Selain denitrifikasi biologi, proses penghilangan nitrat antara lain dapat dilakukan dengan teknologi reverse osmosis, elektrodialisa, penukar ion, dan denitrifikasi kimia maupun adsorpsi [20].…”
Section: Gambar 8 Grafik Efisiensi Penurunan Nitrat Pada Teknologi Ounclassified
“…As a result, a number of methods were used for the removal of NO 3 − contamination. The top three treatment methods which were applied full-scale for NO 3 − removal involves ion exchange, electrodialysis and reverse osmosis [ 14 , 15 ]. Each process appears to have a number of disadvantages and limitations.…”
Section: Introductionmentioning
confidence: 99%